Analisis Multilevel Faktor Resiko Stunting di Indonesia: Sebuah Tinjauan Literatur - Nelly Yuana; Ta. Larasati; Khairun Nisa Berawi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Stunting can cause poverty and create a vicious circle because stunting can increase morbidity, mortality and its consequences can extend to adulthood, thus increasing the risk of low newborns, infectious and non-communicable diseases, and decreased productivity and economic income. The prevalence of stunting in Indonesia in 2018 is 30.8% of the government's target of 14% in 2024. The aim of this study was to determine the risk factors for stunting based on multilevel analysis. Leading databases were searched electronically between 2017 and 2021, relevant health databases included PubMed, Google Scholar, and Cochrane using the keywords “multilevel analysis stunting”, “multilevel analysis of stunting determinants”, “multilevel analysis of risk factor stunting”. From 232 articles, 4 articles were identified and included in the review. Some of the risk factors that cause stunting in Indonesia, individual level: male gender, children aged 12-32 months, birth length less than 48 cm, low birth weight (LBW), number of household members more or equivalent with 5 people, living in households with more or equivalent with 3 children under 5 years of age, maternal height less than 150 cm, maternal age at pregnancy less than 20 years and more than 35 years, Antenatal care less than 4 times, household-level: slum, low parental education, community level: active posyandu, living in rural areas, and in areas outside Java-Bali.Abstrak: Stunting dapat meyebabkan kemiskinan dan menciptakan lingkaran setan, karena stunting bisa meningkatkan morbiditas, mortalitas serta konsekwensinya dapat meluas hingga dewasa, sehingga dapat meningkatkan resiko bayi baru lahir rendah, penyakit infeksi dan penyakit tidak menular, serta produktivitas dan pendapatan ekonomi yang menurun. Prevalensi stunting di Indonesia tahun 2018 sebesar 30,8% dari target pemerintah 14% di tahun 2024. Tujuan penelitian untuk mengetahui faktor resiko stunting berdasarkan analisis multilevel. Database terkemuka dicari secara elektronik antara tahun 2017 sampai 2021, database kesehatan yang relevan termasuk PubMed, Google Scholar, dan Cochrane dengan menggunakan kata kunci “multilevel analysis stunting”, “multilevel analysis determinan stunting”, “multilevel analysis risk factor stunting”. Dari 232 artikel didapati 4 artikel diidentifikasi dan dimasukkan dalam ulasan. Beberapa faktor resiko yang menyebabkan stunting di Indonesia, level individu :  jenis kelamin laki-laki, anak usia 12-32 bulan, panjang badan lahir kurang dari 48 cm, berat badan lahir rendah (BBLR), jumlah anggota rumah tangga lebih dari 5 orang, tinggal dalam rumah tangga dengan 3 anak dibawah usia 5 tahun, tinggi badan ibu kurang dari 150 cm, usia ibu saat hamil kurang dari 20 tahun dan lebih dari 35 tahun, Antenatalcare kurang dari 4 kali, level rumah tangga rumah :  kumuh, pendidikan orang tua yang rendah, level komunitas : keaktifan posyandu, tinggal dipedesaan, dan wilayah luar Jawa-Bali.